Analysis of The Effect of Financial Inclusion and Literature Intensity on Financial Technology: Study on Students in Malang City - Dhiya Azami A; Eko Suprayitno (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2022)
In today's modern era technology is not foreign to the people of Indonesia. Almost all Indonesian people use information technology, especially in internet services. Fintech is one method of service in the financial sector that is popular in the digital era. This sector is a factor that is highly expected by the government and the community in increasing access to financial services. This study uses a partial least square (SEM-PLS) structure equation analysis with a tool in the form of SmartPls software and is supported by data from questionnaires distributed to students using fintech services in Malang City. The results obtained from this study are known that financial literacy has a positive and significant effect on financial technology in Malang City Students. This is indicated by the original sample value of 0.028 and the t-statistical value of 13.613. The value of t statistic is greater than the value of t table which is 1.96. Then from this research it is also known that financial inclusion has a positive and insignificant effect on financial technology in Malang City Students. This is indicated by the original sample value of 0.832 and the t-statistical value of 0.454, besides that it is also known that the t-statistical value is smaller than the t-table value of 1.96.